Validation of a 3-D adaptive stable generalized/eXtended finite element method for mixed-mode brittle fracture propagation - Mukhtar, Faisal M.; Alves, Phillipe D.; Duarte, C. Armando (International journal of fracture, 2020)
In this paper, a Stable Generalized/eXtended Finite Element Method (SGFEM) is combined with mesh adaptivity for the robust and computationally efficient simulation of mixed-mode brittle fracture propagation. Both h -refinement around the fracture front and p -enrichment of the analysis domain are used to control discretization errors. A Linear Elastic Fracture Mechanics (LEFM) model based on Griffith’s criterion is adopted. LEFM scaling relations are used at each fracture propagation step to back calculate SIFs that meet Griffith’s criterion. As a result, no iterations are necessary to find loading scaling parameters or fracture size that meets Griffith’s criterion. The method is validated against several experimental data sets for mode I and mode I+II fracture propagation problems. Very good agreement between SGFEM and experimental results is observed. These include fracture path, Crack Opening Displacement (COD), and load and fracture length versus COD curves. The computational efficiency of the method is also assessed.